The climatic effects on infiltration and stability of geotextile reinforced walls. - Albino, Uilian da Rocha (2018)
This study presents the climatic effects (rainfall and evaporation) on the stability of reinforced soil walls constructed with nonwoven geotextiles reinforcements using numerical modeling. The evaluation of the climatic effects was organized in two steps: (1) numerical modeling of the infiltration compared to a laboratory full-scale model of a nonwoven reinforced soil wall and; (2) a numerical investigation of a hypothetical geosynthetic-reinforced soil wall subjected to climatic changes including precipitation and evaporation, for a period of 2 years. The numerical modeling of infiltration into the full-scale model was conducted using two representative hydraulic parameters of backfill soil (suction and volumetric moisture content). The infiltration modeling of the laboratory reinforced structure was conducted to provide better understanding around the hydraulic behavior and water path into regions not measured by instrumentation during laboratory tests. Numerical calibration was conducted in order to capture the capillary break developed at soil-geotextile interfaces, including the anchorage of the reinforcements in the wrap-around facing. As a second step of this study, a hypothetical reinforced soil wall constructed with nonwoven geotextile was modeled using the same hydraulic properties of soil and geotextile used in the previously described numerical modeling. The climatic changes were simulated considering the water balance at ground surface. The climatic effects on the reinforced soil wall were assessed by the use of soil suction changes and consequent influences on the factors of safety over 2 years of operation. Results from numerical simulation of infiltration into the laboratory model indicated that water breakthrough did not occur uniformly along the length of the geotextile. In addition, numerical infiltration into the laboratory model showed that the water path into the reinforced zone is influenced by the anchorage of the reinforcement in the wrap-around facing. The results of the climatic variations in the hypothetical structure showed that approximately 50% of potential evaporation and total rainfall effectively evaporates and infiltrates. Also, the results revealed that the capillary barrier did not generate significant surface runoff and did not reduce the effective infiltration in the reinforced zone. On the other hand, water was observed to advance faster outside of the reinforced zone than inside of the reinforced zone because of the capillary barrier. Additionally, simulations showed that soil inside of the reinforced zone never recovered its initial suction value after first wetting because the capillary barrier restricted evaporation. Results also revealed that increases in global factor of safety, after first wetting of the geotextile reinforced soil wall, occurred because of the increases in soil suction of the first reinforced layer. Lastly, cumulative precipitation during successive days of rainfall showed some correlation to changes in global factor of safety.